2006
DOI: 10.1177/003335490612100406
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Intimate Partner Violence and Their Associations with Physical Health, Psychological Distress, and Substance Use

Abstract: More attention to the ways in which interpersonal violence is conceptualized, measured, and screened for is crucial. Specifically, while women have greater exposure to IPV, and subsequently a greater range of health problems, the effects on men should not be ignored.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

25
266
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 259 publications
(298 citation statements)
references
References 30 publications
25
266
1
Order By: Relevance
“…[28][29][30][31][32][34][35][36][51][52][53][54][55][56][57][58][59][60][61] Significantly higher percentages of women who were HIV-positive, had experienced IPV in the past year, and had used hard drugs in the past 30 days exhibited higher depressive symptoms, without adjusting for sociodemographic factors. However, when adjusting for the other SAVA factors, sociodemographic factors, social support and alcohol abuse, only the experience of IPV in the past year and drug use in the past 30 days remained significant, as did reporting low social support.…”
Section: Discussionmentioning
confidence: 99%
“…[28][29][30][31][32][34][35][36][51][52][53][54][55][56][57][58][59][60][61] Significantly higher percentages of women who were HIV-positive, had experienced IPV in the past year, and had used hard drugs in the past 30 days exhibited higher depressive symptoms, without adjusting for sociodemographic factors. However, when adjusting for the other SAVA factors, sociodemographic factors, social support and alcohol abuse, only the experience of IPV in the past year and drug use in the past 30 days remained significant, as did reporting low social support.…”
Section: Discussionmentioning
confidence: 99%
“…Numerous studies show that relationship violence during childhood and adulthood is associated with poorer mental health in adulthood. [8][9][10][11][12][13][14][15][16][17][18][19][20] Although it is difficult to establish the temporal order of the association between relationship violence and mental health status, 21 available longitudinal research is generally consistent with the idea that violence experiences may actually lead to greater psychological distress. 12 The effects of relationship violence on mental health are also generally consistent across a wide range of violence measures, including nonspecific violence and victimization, violence during childhood, physical assault, psychological aggression, and sexual coercion.…”
Section: Introductionmentioning
confidence: 99%
“…Depression, anxiety and PTSD, all established by means of a diagnostic interview, was associated with intimate partner violence against women but not men in one study (Ehrensaft, Moffitt and Caspi, 2006), while others found that both men and women exposed to intimate partner violence reported symptoms of depression (Coker et al, 2002a). It is often reported that women suffer more severe health consequences in the aftermath of victimization, which is sometimes taken as a sign that women are exposed to more severe forms of intimate partner violence (Carbone-Lopez, Kruttschnitt and Macmillan, 2006;Afifi et al, 2009).…”
Section: Intimate Partner Violence and Ill-healthmentioning
confidence: 99%